Automatic method to calculate the storage volume of refrigerator assembly based on binary voxel images. (17th November 2021) - Fu, Jianhui; Jung, Yoongho; Wang, Jin; Lu, Guodong; Wang, Wei; Zhang, Xinwei
ABSTRACT: The storage volume of a refrigerator is an important consideration for design and purchase. However, the inner space of a refrigerator assembly is not delimited, because of the holes and gaps between parts. The traditional calculation method for the storage volume reconstructs the boundaries of the inner space by artificially filling holes and gaps, which is labor-intensive and time-consuming. We present a boundary surface reconstruction method based on binary images for automatically calculating the storage volume of a refrigerator assembly. First, the components facing the inner space are represented by a voxel model. Then, holes and gaps are filled on the basis of a binary image to form a closed voxel boundary so that the inner space can be determined. The boundary surface enclosing the storage space is reconstructed by using a modified dual contouring algorithm constrained by intersection points between the boundary voxels and assembly. Finally, the storage volume is calculated from the reconstructed surface. A prototype system was developed to verify the proposed algorithm. The results showed that the reconstructed boundary surface clung to the inside wall of the refrigerator assembly, and the transitions across the holes and gaps were smooth and continuous.